Allogeneic transplantation for advanced acute myeloid leukemia: The value of complete remission. Issue 11 (24th January 2017) - Weisdorf, Daniel J.; Millard, Heather R.; Horowitz, Mary M.; Hyare, Parvinder S.; Champlin, Richard; Ho, Vincent; Mielcarek, Marco; Rezvani, Andrew; Stockerl‐Goldstein, Keith; Khoury, Hanna J.; De Lima, Marcos; Saber, Wael; et al.
Abstract : BACKGROUND: Patients with acute myeloid leukemia (AML) without complete remission (CR) or in first relapse (Rel1) can have extended leukemia control and survival after allogeneic hematopoietic cell transplantation (HCT). For patients in Rel1 or primary induction failure (PIF), transplantation versus treatment to achieve a second CR (CR2) and subsequent HCT might yield similar outcomes, but available comparative data are scarce. METHODS: Survival was analyzed in 4682 HCT recipients according to disease status: PIF (N = 1440), Rel1 (failing ≥1 reinduction; N = 1256), and CR2 (N = 1986). RESULTS: Patient, disease, and transplantation characteristics were similar, except that patients in CR2 more often had performance scores of 90% to 100%, de novo AML, and longer CR1 duration. Adverse cytogenetics were more common in patients who experienced PIF. The 5‐year survival rate adjusted for performance score, cytogenetic risk, and donor type for CR2 was 39% (95% confidence interval [CI], 37%‐41%) compared with 18% (95% CI, 16%‐20%) for HCT in Rel1 and 21% (95% CI, 19%‐23%) in PIF ( P < .0001). CONCLUSIONS: Although survival is superior for patients who undergo HCT in CR2, transplantation for selected patients in Rel1 or PIF may still be valuable. These data can guide decision making about additional salvage therapy versus prompt HCT for patients not in CR, but they also highlight that AML is intrinsically more treatable in patients who have favorable‐risk cytogenetics, those with longer CR1 duration, and younger patients with better performance status. Cancer 2017;123:2025–2034 . © 2017 American Cancer Society . Abstract : Allogeneic hematopoietic cell transplantation can cure some patients with acute myeloid leukemia who achieve complete remission, but the comparative outcomes after transplantation for those who fail to achieve complete remission (primary induction failure), fail in first relapse, or fail in second complete remission are not well studied. By using left‐truncated, time‐to‐event, multivariable regression, the comparative outcomes of hematopoietic cell transplantation in these 3 states are compared in order to guide expectations for clinical decision making about transplantation for patients with acute myeloid leukemia not in complete remission.